Machining method for controlling coercive force of rotor
By screening small-axle raw materials with high nickel content and vacuum annealing, the metallographic structure of the small-axle is improved, and the problems of low pass rate for rotor coercive force processing and poor coercive force stability after low temperature are solved, thereby improving the pass rate for rotor coercive force and ensuring stability.
Patent Information
- Application Number
- CN202411661557.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the process method for synthesizing rotors with magnets and small axle pressing has problems such as low pass rate of rotor coercive force processing and poor coercive force stability after the rotor is assembled by the product at low temperature.
By screening the nickel element content in the small-axis raw material 1Cr18Ni9Ti, the small-axis raw material 1Cr18Ni9Ti is greater than or equal to the preset content threshold, and the small-axis is heat treated to the small-axis to improve its metallographic structure, thereby eliminating the coercive force generated by the small-axis processing.
The pass rate of rotor coercive force processing is improved from 65% to 100%, and the coercive force stability is maintained after low-temperature debugging, so that the pass rate of rotor coercive force is continuously controlled at 100%.
Smart Images

Figure CN119582544A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rotor processing, and in particular relates to a processing method for controlling the coercive force of a rotor. Background Art
[0002] The rotor is formed by pressing together the magnet and the small shaft. Before the combination, the magnet and the small shaft are left with margins. After the rotor is formed by pressing together, it is precisely processed. In addition to ensuring the final size of the design drawing, the coercive force of the rotor is not more than 100A / m. The raw material of the magnet is electrical pure iron DT4E-hot rolling, standard GB / T6984-1986, and the design drawing requires the coercive force to be no more than 48A / m; the raw material of the small shaft is 1Cr18Ni9Ti-hot rolling, standard GB / T1220-1992. During the processing, it is necessary to process the straight lines m0.2GB6403.3-2008, and the outer circle of the straight lines and the magnet The hole is an interference fit. The two-dimensional and three-dimensional diagrams of the rotor assembly are as follows Figure 1 .
[0003] The raw material of the small shaft is 1Cr18Ni9Ti-hot-rolled, which is a non-magnetic austenitic stainless steel. Under normal circumstances, the parts processed by this material should not have coercive magnetism. However, during the processing, the small shaft straight grain m0.2GB6403.3-2008 is mechanically extruded by a knurling cutter, which is prone to metallographic changes, grain size increases, and changes from non-magnetic austenite to strongly magnetic martensite. The small shaft will produce coercive magnetism, resulting in excessive coercive magnetism of the rotor, which ultimately affects the processing pass rate of the rotor coercive magnetism. In order to eliminate the coercive magnetism generated by the small shaft processing, heat treatment is added to change the internal organizational structure of the material. The usual heat treatment method is solid solution treatment. However, there are two problems with adding solid solution treatment: one is the variability of the parts; the other is that the coercive magnetism generated by the small shaft processing still exists and cannot be eliminated.
[0004] The rotor is formed by pressing qualified magnets and small shafts together, and then precision machining is performed on the rotor. The last step of the process requires measuring whether the coercive force is no more than 100A / m to determine whether it is qualified. The qualified rate of each batch is very low, and the qualified rate is generally concentrated at around 65%. This has been a technical problem that has not been solved for many years, and has seriously restricted the supporting output of the entire set of products. The production department can only adopt the method of increasing large investments and selecting small quantities to meet the needs of product matching.
[0005] In addition, after the rotor was manufactured with qualified coercive force according to the original process method, the coercive force of the rotor increased beyond the tolerance after the rotor entered the product assembly and low-temperature debugging at -55℃, affecting the stability of the product performance indicators, seriously restricting the assembly and debugging of the product, and even more seriously affecting the supply demand of the product market.
[0006] Therefore, the current process of pressing the magnet and the small shaft into a rotor has the problems of low rotor coercive magnetic force processing qualification rate and poor coercive magnetic force stability of the rotor after product assembly at low temperature. Summary of the invention
[0007] The purpose of the present invention is to provide a processing method for controlling the coercive force of a rotor to solve the problems of low rotor coercive force processing qualification rate and poor coercive force stability of the rotor after product assembly at low temperature in the current process of pressing a magnet and a small shaft into a rotor.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] This specification provides a processing method for controlling the coercive force of a rotor, comprising:
[0010] Step 102, screening and obtaining small shaft raw material 1Cr18Ni9Ti with a nickel content greater than or equal to a preset content threshold;
[0011] Step 104, mechanically extruding the raw material 1Cr18Ni9Ti of the small shaft by using a knurling cutter to obtain a small shaft with straight grain m0.2GB6403.3-2008;
[0012] Step 106, performing vacuum annealing treatment on the small shaft of straight grain m0.2GB6403.3-2008 to obtain the small shaft after vacuum annealing treatment;
[0013] Step 108, pressing the small shaft after vacuum annealing and the processed magnet together to obtain a rotor whose coercive force meets preset requirements.
[0014] Based on the above technical solution, this specification can achieve the following technical effects:
[0015] The method improves the metallographic structure change of the small shaft straight grain m0.2GB6403.3-2008 during the mechanical extrusion molding process using a knurling cutter by adding a heat treatment method of vacuum annealing of the small shaft, and improves the change from larger grains to smaller grains, and changes from strongly magnetic martensite to non-magnetic austenite, thereby eliminating the coercive force generated by the small shaft processing; in addition, by screening the nickel element content in the small shaft raw material 1Cr18Ni9Ti to be greater than or equal to a preset content threshold, the nickel (Ni) element content is higher, and the 1Cr18Ni9Ti stainless steel is more non-magnetic or has low magnetism, thereby improving the stability of the coercive force of the rotor after low-temperature debugging after the rotor is installed in the product, thereby solving the problems of low rotor coercive magnetic force processing qualification rate and poor coercive magnetic force stability of the rotor after low-temperature product assembly in the current process method of pressing the magnet and the small shaft into a rotor. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1The figure is a flow chart of a processing method for controlling the coercive force of a rotor in one embodiment of the present invention.
[0017] Figure 2 2D and 3D diagrams of a rotor assembly in one embodiment of the present invention.
[0018] Figure 3 2D diagram of the minor axis in one embodiment of the present invention. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The advantages and features of the present invention will become more apparent from the following description and claims. It should be noted that the drawings are all in very simplified form and are not in precise proportions, and are only used to conveniently and clearly assist in explaining the purpose of the embodiments of the present invention.
[0020] It should be noted that, in order to clearly explain the content of the present invention, the present invention specifically cites multiple embodiments to further illustrate different implementations of the present invention, wherein the multiple embodiments are enumerated rather than exhaustive. In addition, for the sake of brevity of explanation, the contents mentioned in the previous embodiments are often omitted in the subsequent embodiments. Therefore, the contents not mentioned in the subsequent embodiments can refer to the previous embodiments accordingly.
[0021] Example 1
[0022] Please refer to Figure 1 , Figure 1 A processing method for controlling the coercive force of a rotor provided in this embodiment is shown. In this embodiment, the method includes:
[0023] Before step 102, the method further includes:
[0024] Analysis of small shaft raw material 1Cr18Ni9Ti
[0025] The influence of several elements on the coercive force of the rotor is obtained to obtain the target element with the greatest influence on the coercive force of the rotor; the target element is nickel;
[0026] In this embodiment, the several elements include carbon, chromium, nickel, titanium, silicon, manganese, and sulfur.
[0027] Step 102, screening and obtaining small shaft raw material 1Cr18Ni9Ti with a nickel content greater than or equal to a preset content threshold;
[0028] In this embodiment, one implementation of step 102 is:
[0029] Step 202, processing a plurality of small shaft raw materials 1Cr18Ni9Ti with different nickel content into formed small shafts and cooperating with the processed magnets to form a rotor;
[0030] In this embodiment, one implementation of step 202 is:
[0031] Step 302, obtaining nickel content of small shaft raw materials 1Cr18Ni9Ti of different types and arranging them in ascending order to obtain a small shaft nickel content list; each nickel content in the list corresponds to at least one type of small shaft raw material 1Cr18Ni9Ti;
[0032] Step 304, performing small shaft forming processing on the small shaft raw material 1Cr18Ni9Ti of each model in the small shaft nickel element content list in turn and pressing processing with the processed magnets to obtain rotors corresponding to several models; the small shaft forming processing includes vacuum annealing treatment.
[0033] Step 204, after the rotor is loaded into the product, a low-temperature -55°C coercive force test is performed to obtain the coercive force test result of the rotor and obtain a preset content threshold based on the test result;
[0034] In this embodiment, one implementation of step 204 is:
[0035] Step 404, sequentially install several models of rotors into the product to perform a low temperature coercive force test at -55°C to determine whether the rotor coercive force is out of tolerance, and obtain coercive force test results of rotors corresponding to several models;
[0036] Step 406: Based on a number of coercive force test results, the lowest nickel content for which the rotor coercive force does not exceed the tolerance is used as a preset content threshold.
[0037] Step 206 , screening the small shaft raw material 1Cr18Ni9Ti based on the preset content threshold, and obtaining the small shaft raw material 1Cr18Ni9Ti with a nickel element content greater than or equal to the preset content threshold.
[0038] In this embodiment, one implementation of step 206 is to obtain several types of small shaft raw materials 1Cr18Ni9Ti with nickel element content greater than or equal to the preset content threshold based on the preset content threshold and the small shaft nickel element content list.
[0039] In this embodiment, the preset content threshold is 9.5%.
[0040] Step 104, mechanically extruding the raw material 1Cr18Ni9Ti of the small shaft by using a knurling cutter to obtain a small shaft with straight grain m0.2GB6403.3-2008;
[0041] Step 106, performing vacuum annealing treatment on the small shaft of straight grain m0.2GB6403.3-2008 to obtain the small shaft after vacuum annealing treatment;
[0042] In this embodiment, the parameters of the vacuum annealing treatment are as follows: vacuumizing the small shaft of the straight-grained m0.2GB6403.3-2008, heating it to 1000° C. to 1100° C., keeping it at that temperature for 60 min to 80 min, and then cooling it by nitrogen filling.
[0043] Step 108, pressing the small shaft after vacuum annealing and the processed magnet together to obtain a rotor whose coercive force meets preset requirements.
[0044] In this embodiment, the preset requirement is that the coercive force of the rotor is not greater than 100 A / m.
[0045] In this embodiment, it also includes:
[0046] The influence of several elements in the raw material 1Cr18Ni9Ti of the small shaft on the coercive force of the rotor is analyzed, and the target element with the greatest influence on the coercive force of the rotor is obtained; the target element is nickel.
[0047] In this embodiment, the several elements include carbon, chromium, nickel, titanium, silicon, manganese, and sulfur.
[0048] Specifically, the rotor is formed by pressing together two parts, the magnet and the small shaft. After the rotor is formed by pressing together, it is precision machined. In addition to ensuring the final size of the design drawings, the coercive force of the rotor is not more than 100A / m. The raw material of the magnet is DT4E-hot rolling, standard GB / T6984-1986, and the design drawings require that the coercive force is not more than 48A / m; the raw material of the small shaft is 1Cr18Ni9Ti-hot rolling, standard GB / T1220-1992, and the outer circle of the straight-line part is matched with the φ3.5H7 hole of the magnet, which is an interference fit. The two-dimensional and three-dimensional drawings of the rotor assembly are shown in the figure. Figure 2 .
[0049] Description of rotor structure: Before the rotor is assembled, except for the matching parts of the magnet and the small shaft that are processed to the final size, the rest of the magnets and the small shaft are left with margins. After the rotor is formed by pressing, it is precision machined. In addition to ensuring the final size of the design drawing, the coercive force of the rotor is not greater than 100A / m. The processing of the magnets can ensure the dimensional accuracy based on the existing equipment resources, and the coercive force of not more than 48A / m required by the design drawings can also be guaranteed, and there is no effect on the coercive force of the rotor; the processing of the small shaft can ensure the dimensional accuracy based on the existing equipment resources, but the processing of the straight grain m0.2GB6403.3-2008 adopts knurling knife mechanical extrusion molding, which is prone to metallographic changes. The small shaft will produce coercive force, resulting in excessive coercive force of the rotor. The two-dimensional diagram of the small shaft is as follows Figure 3 shown.
[0050] The rotor is formed by pressing qualified magnets and small shafts together, and then precision machining is performed on the rotor. The last step of the process requires measuring whether the coercive force is no more than 100A / m to determine whether it is qualified. The qualified rate of each batch is very low, and the qualified rate is generally concentrated at around 65%. This has been a technical problem that has not been solved for many years, and has seriously restricted the supporting output of the entire set of products. The production department can only adopt the method of increasing large investments and selecting small quantities to meet the needs of product matching.
[0051] In addition, after the rotor was manufactured with qualified coercive force according to the original process method, the coercive force of the rotor increased beyond the tolerance after the rotor entered the product assembly and low-temperature debugging at -55℃, affecting the stability of the product performance indicators, seriously restricting the assembly and debugging of the product, and even more seriously affecting the supply demand of the product market.
[0052] Therefore, the current prior art has the following shortcomings:
[0053] (1) The design drawing material of the small shaft is 1Cr18Ni9Ti-hot rolled, and there is no heat treatment requirement; (2) The usual heat treatment method for 1Cr18Ni9Ti stainless steel material is solid solution treatment. Preliminary tests have shown that solid solution treatment cannot eliminate the coercive force generated by the small shaft processing; (3) The usual process for machining parts is not to arrange a low-temperature treatment process at -55°C. It is difficult to find that the nickel (Ni) content in the raw material 1Cr18Ni9Ti has the greatest impact on the coercive force of the rotor; (4) The method of increasing large-scale investment and selecting small quantities results in high production costs and low rotor qualification rate.
[0054] Therefore, in this embodiment, in order to eliminate the coercive force generated by the small shaft processing, the heat treatment method of vacuum annealing of the small shaft is added to improve the metallographic structure change of the small shaft straight grain m0.2GB6403.3-2008 during the mechanical extrusion molding using a knurling cutter, from the grain enlargement to the grain reduction, from the strong magnetic martensite to the non-magnetic austenite, to eliminate the coercive force generated by the small shaft processing. Vacuum annealing parameters: after vacuuming, the temperature is raised to 1000℃~1100℃, kept warm for 60min~80min, and cooled with nitrogen. Through batch production verification, vacuum annealing can improve the internal structure of the material, eliminate the coercive force generated by the small shaft processing, and increase the rotor coercive force qualification rate from 65% to 100%.
[0055] In order to solve the problem of poor stability of the coercive force of the rotor after the product is debugged at a low temperature of -55℃, the influence of the content of each element in the small shaft raw material 1Cr18Ni9Ti on the coercive force of the rotor is analyzed. 1Cr18Ni9Ti is a common austenitic stainless steel. Generally, austenitic stainless steel 1Cr18Ni9Ti has no magnetism or low magnetism. However, under specific conditions of -55℃, the magnetism of stainless steel may change, among which the nickel (Ni) element content has the greatest influence on the magnetic properties. Nickel can improve the antimagnetic properties of stainless steel, making stainless steel more non-magnetic or low-magnetic. Therefore, the higher the nickel (Ni) element content, the more non-magnetic or low-magnetic 1Cr18Ni9Ti stainless steel. Through batch production verification, the method of selecting the nickel (Ni) element content of the small shaft raw material greater than or equal to 9.5% is used to improve the stability of the coercive force of the rotor after the low temperature debugging of -55℃, so that the qualified rate of the rotor coercive force continues to be controlled at 100%.
[0056] Based on this, the method increases the rotor coercive force qualification rate from 65% to 100% by adding a heat treatment method of vacuum annealing of the small shaft; in addition, by screening the small shaft raw material with a nickel (Ni) element content greater than or equal to 9.5%, the stability of the coercive force of the rotor installed product after low-temperature debugging at -55°C is improved, so that the rotor coercive force qualification rate continues to be controlled at 100%.
[0057] In summary, the method improves the metallographic structure change of the small shaft straight grain m0.2GB6403.3-2008 during the mechanical extrusion molding process using a knurling cutter by adding a heat treatment method of vacuum annealing of the small shaft, and improves the change from larger grains to smaller grains, and transforms from strongly magnetic martensite to non-magnetic austenite, thereby eliminating the coercive force generated by the small shaft processing; in addition, by screening the nickel content in the small shaft raw material 1Cr18Ni9Ti to be greater than or equal to a preset content threshold, the nickel (Ni) element content is higher, and the 1Cr18Ni9Ti stainless steel is more non-magnetic or low-magnetic, thereby improving the stability of the coercive force of the rotor after low-temperature debugging after the rotor is installed in the product, thereby solving the problems of low rotor coercive magnetic processing qualification rate and poor coercive magnetic stability of the rotor after low-temperature assembly of the product in the current process method of pressing the magnet and the small shaft into a rotor.
[0058] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A processing method for controlling the coercive force of a rotor, characterized in that: include: Screening and obtaining small shaft raw material 1Cr18Ni9Ti with a nickel content greater than or equal to a preset content threshold; The raw material 1Cr18Ni9Ti of the small shaft is mechanically extruded by a knurling cutter to obtain a small shaft with straight grain m0.2GB6403.3-2008; The small shaft of straight grain m0.2GB6403.3-2008 is subjected to vacuum annealing treatment to obtain the small shaft after vacuum annealing treatment; The small shaft after vacuum annealing is pressed together with the processed magnet to obtain a rotor whose coercive force meets the preset requirements.
2. The method according to claim 1, characterized in that The step of screening and obtaining the small shaft raw material 1Cr18Ni9Ti whose nickel element content is greater than or equal to the preset content threshold comprises: Several small shaft raw materials 1Cr18Ni9Ti with different nickel content are processed into formed small shafts and matched with the processed magnets to form rotors; After the rotor is installed in the product, a low-temperature -55°C coercive force test is performed to obtain the coercive force test result of the rotor and obtain a preset content threshold based on the test result; The small shaft raw material 1Cr18Ni9Ti is screened based on the preset content threshold to obtain the small shaft raw material 1Cr18Ni9Ti with a nickel element content greater than or equal to the preset content threshold.
3. The method according to claim 2, characterized in that The steps of processing a plurality of small shaft raw materials 1Cr18Ni9Ti with different nickel content into formed small shafts and cooperating with the processed magnets to form a rotor include: Obtain the nickel content of small shaft raw materials 1Cr18Ni9Ti of different models and arrange them in ascending order to obtain a small shaft nickel content list; each nickel content in the list corresponds to at least one model of small shaft raw material 1Cr18Ni9Ti; The small shaft raw material 1Cr18Ni9Ti of each model in the small shaft nickel element content list is subjected to small shaft forming processing in turn and pressed together with the processed magnet to obtain the rotor corresponding to each model; the small shaft forming processing includes vacuum annealing treatment.
4. The method according to claim 3, characterized in that The steps of loading the rotor into the product and performing a low-temperature -55°C coercive force test, obtaining the coercive force test result of the rotor and obtaining a preset content threshold based on the test result include: Each model of rotor is installed into the product in turn for a low-temperature coercive force test at -55°C to determine whether the rotor coercive force is out of tolerance and obtain the coercive force test results of the rotor corresponding to each model; Based on several coercive force test results, the lowest nickel content for which the rotor coercive force does not exceed the tolerance is taken as the preset content threshold.
5. The method according to claim 4, characterized in that The method of screening the small shaft raw material 1Cr18Ni9Ti based on the preset content threshold and obtaining the small shaft raw material 1Cr18Ni9Ti with a nickel element content greater than or equal to the preset content threshold is to obtain several models of small shaft raw materials 1Cr18Ni9Ti with a nickel element content greater than or equal to the preset content threshold based on the preset content threshold and the small shaft nickel element content list.
6. The method according to claim 5, characterized in that The preset content threshold is 9.5%.
7. The method according to claim 1, characterized in that The parameters of the vacuum annealing treatment are as follows: vacuumizing the small axis of the straight-grained m0.2GB6403.3-2008, heating it to 1000° C. to 1100° C., keeping it at that temperature for 60 min to 80 min, and then cooling it by nitrogen filling.
8. The method according to claim 1, characterized in that The preset requirement is that the coercive force of the rotor is no greater than 100 A / m.